Intelligence: the psychological view - Funke, Joachim (Intelligence, 2022)
This chapter presents a small sample of psychological research on the topic of “human intelligence.” Intelligence is a central construct in modern psychology for describing differences in cognitive performance. Somewhat broader conceptualizations view human adaptation to the environment and shaping the environment to our advantage as central to intelligent action. A brief overview of different conceptions of intelligence is given. The “dark side” of intelligence (the destructive potential) is also addressed. The peculiarities of human intelligence compared to artificial intelligence are emphasized.
Gesehen am 31.08.2022